АЛТЕРНАТИВНИ МЕТОДИ РЕШАВАЊА КРИВИЧНИХ ПРЕДМЕТА - Maksimović, Bogdana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2026)
Alternative methods of resolving criminal cases represent a significant instrument of contemporary criminal procedural law, as they alleviate the judicial system, accelerate proceedings, and can achieve greater fairness for the defendant, though not necessarily for the injured party. In domestic legislation, two mechanisms stand out – the conditional deferral of criminal prosecution and the plea agreement – which differ in origin but share the purpose of ensuring efficiency and humanization of the criminal procedure. The conditional deferral of criminal prosecution emerged as a way to resolve minor offenses without a formal trial, involving the suspect in taking responsibility and remedying consequences. The prosecutor may defer prosecution if the suspect voluntarily accepts one or more legal obligations, such as compensation, payment for humanitarian purposes, community service, addiction treatment, or psychosocial therapy. Once fulfilled, the criminal complaint is dismissed, no proceedings are conducted, no sanction is imposed, and the suspect is not entered into the criminal register. This relieves the judiciary, may satisfy the injured party through restitution, and offers the suspect resocialization and avoidance of stigma. However, the injured party’s role remains minimal, even when benefiting from compensatory obligations. The plea agreement allows the defendant to admit the offense in exchange for a more lenient sanction or more favorable treatment, thereby shortening proceedings, reducing costs, and relieving courts, while giving parties greater procedural certainty. Although essentially a contractual arrangement initiated by the prosecutor or defense, the court controls legality and voluntariness, protecting the defendant’s rights. Defense counsel is mandatory to ensure the defendant understands the consequences. As with conditional deferral, the injured party’s interests are only indirectly protected, since efficiency and agreement between prosecution and defense dominate. An empirical analysis of the Basic Public Prosecutor’s Office in Novi Sad (2014–2023) showed clear trends in applying conditional deferral and plea agreements. In this period, 49,578 criminal complaints were filed, with 14,694 resolved through conditional deferral and 2,652 through plea agreements, reducing judicial workload by 34.99 %. Conditional deferral was applied more often (29.64 %) than plea agreements (5.35 %). After 2015, when both reached their peak (48.25 % of complaints), their application has continuously declined, falling to around 19 % in the last two years. With the decrease in criminal complaints (6,309 in 2014 to 4,226 in 2022), the use of these institutes dropped even more sharply, indicating other factors – legislative changes, judicial practice, criminal policy, and parties’ trust. This raises questions such as whether plea agreements work only for simpler cases while courts remain burdened with complex ones, or whether the injured party’s position should be strengthened in deciding on conditional deferral or concluding a plea agreement.